Greasing the wheels of entrepreneurship? The impact of regulations and corruption on firm entry - Axel Dreher; Martin Gassebner (ETH Zurich, KOF Swiss Economic Institute, 2007)
The paper investigates whether the impact of regulations on entrepreneurship depends on corruption. We first test whether regulations robustly deter firm entry into the markets. Our results show that some regulations are indeed important determinants of entrepreneurial activity. Specifically, more procedures required to start a business and larger minimum capital requirements are detrimental to entrepreneurship. Second, we test whether corruption reduces the negative impact of regulations on entrepreneurship in highly regulated economies. Our empirical analysis for a maximum of 43 countries over the period 2003-2005 shows that corruption is beneficial in highly regulated economies. At the maximum level of regulation among our sample of countries, corruption significantly increases entrepreneurial activity. Our results thus provide support for the grease the wheels hypothesis.
Keywords: D73; F59; M13; L26; 330; corruption; start-ups; grease the wheels; entrepreneurship; regulation; doing business; Unternehmensgründung; Entrepreneurship-Ansatz; Regulierung; Markteintritt; Korruption; Schätzung; Welt